Cost-effectiveness evaluation of different control strategies for Clonorchis sinensis infection in a high endemic area of China: A modelling study. - Yun-Ting He; Xiao-Hong Huang; Yue-Yi Fang; Qing-Sheng Zeng; Lai-De Li; Le Luo; Ying-Si Lai (Public Library of Science (PLoS), 2022)
Clonorchiasis is an important food-borne parasitic disease caused by Clonorchis sinensis infection. The evaluation of long-term cost-effectiveness of control strategies is important for disease control and prevention. The present study aimed to assess the cost-effectiveness of the three recommended strategies (i.e., WHO, Chinese and Guangdong strategies) and different combinations of commonly used measures (i.e., preventive chemotherapy, information, education, and communication (IEC) and environmental improvement) on clonorchiasis. The study area, Fusha town in Guangdong Province, was a typical high endemic area in China. The analysis was based on a multi-group transmission model of C. sinensis infection. We set the intervention duration for 10 years and post-intervention period for 50 years. The corresponding costs and DALYs were estimated. Strategies with incremental cost-effectiveness ratios (ICERs) less than 1/5 of the willingness-to-pay threshold were identified as highly cost-effective strategies. The optimal control strategy was obtained using the next best comparator method. The ICERs of Guangdong strategy were $172 (95% CI: $143-$230) US for praziquantel and $106 (95% CI: $85-$143) US for albendazole, suggesting the highest cost-effectiveness among the three recommended strategies. For praziquantel, 470 sets of control strategies were identified as highly cost-effective strategies for achieving infection control (prevalence<5%). The optimal strategy consisted of chemotherapy targeted on at-risk population, IEC and environmental improvement, with coverages all being 100%, and with the ICER of $202 (95% CI: $168-$271) US. The results for transmission control (prevalence<1%) and albendazole were obtained with the same procedures. The findings may help to develop control policies for C. sinensis infection in high endemic areas. Moreover, the method adopted is applicable for assessment of optimal strategies in other endemic areas.